Letter of Sultan Mahmud Riayat Syah to Governor-General Batavia Sir Willem Arnold Alting the Library of Leiden University collections: does it have diplomatic features? - Noor Muhammad, Salmah Jan; van Engelenhoven, Aone; Abdul Rahman, Nadiatul Shakinah (Human Resource Management Academic Research Society, 2020)
Letter from Sultan Mahmud of Riah Syah from the State of Johore and Pahang addressed to Governor-General Willem Arnold Alting dated on 12 Ramadhan 1211 or March 11, 1797. It is a letter written in handwritten Jawi, beautifully illustrated and preserved in the Leiden University Library. In this sense, the question that might be raised is does this beautiful letter has diplomatic features in it? Therefore, the objective of this study is to identify and analyze diplomatic content through this delivery portal. The library methodology and diplomacy of Islamic theory will be applied in this study. Expectations of the findings show that indeed these poles have diplomatic features that can strengthen relations between governments. Hence, it is expected that the results of this study may help researchers to identify and study the letters of various aspects of the Malay sultanate.